One-step synthesis of three-dimensional Co(OH)2/rGO nano-flowers as enzyme-mimic sensors for glucose detection. (20th April 2018) - Jiang, Danfeng; Chu, Zhenyu; Peng, Jingmeng; Luo, Jingyi; Mao, Yangyang; Yang, Pengqi; Jin, Wanqin
Abstract: Currently, most metal oxides- or hydroxides-based and non-enzymatic sensors require a high alkali concentration in the working environment. Here, we designed a novel non-enzymatic sensor based on a 3D nanostructured Co(OH)2 /rGO film to address this issue. The architecture of the hybrid film was in-situ constructed by the dense assembly of 200 nm flower-like Co(OH)2 crystals bridged by rGO nanosheets. This structure possessed an extremely large specific surface area and an excellent conductivity which were beneficial for adsorbing OH to produce oxidative CoOOH or CoO2, even in a low alkaline condition. This material was able to mimic the functionality of glucose oxidase to oxidize glucose to gluconolactone and exhibited a good sensitivity at a wide alkaline range from 5 × 10 −3 to 1 mol L −1 NaOH solution. Moreover, this sensor showed a wide linear range, excellent selectivity, reproducibility and stability for real blood analysis. Highlights: A flower-like Co(OH)2 /rGO nano-composite film was in-situ prepared by a facile hydrothermal method. This architecture can effectively capture OH − to mimic the function of glucose oxidase under a very low alkali environment. The as-prepared biosensor shows ultrahigh sensitivity at a very wide range of alkali concentration from 5 × 10 −3 M to 1 M.